The added value of kinematic evaluation of the timed finger-to-nose test in persons post-stroke. Issue 1 (December 2017) - Johansson, Gudrun; Grip, Helena; Levin, Mindy; Häger, Charlotte
Abstract Background Upper limb coordination in persons post-stroke may be estimated by the commonly used Finger-to-Nose Test (FNT), which is also part of the Fugl-Meyer Assessment. The total movement time (TMT) is used as a clinical outcome measure, while kinematic evaluation also enables an objective quantification of movement quality and motor performance. Our aims were to kinematically characterize FNT performance in persons post-stroke and controls and to investigate the construct validity of the test in persons with varying levels of impairment post-stroke. Methods A three-dimensional motion capture system recorded body movements during performance of the FNT in 33 persons post-stroke who had mild or moderate upper limb motor impairments (Fugl-Meyer scores of 50–62 or 32–49, respectively), and 41 non-disabled controls. TMT and kinematic variables of the hand (pointing time, peak speed, time to peak speed, number of movement units, path ratio, and pointing accuracy), elbow/shoulder joints (range of motion, interjoint coordination), and scapular/trunk movement were calculated. Our analysis focused on the pointing phase (knee to nose movement of the FNT). Independentt or Mann-Whitney U tests and effect sizes were used to analyze group differences. Sub-group analyses based on movement time and stroke severity were performed. Within the stroke group, simple and multiple linear regression were used to identify relationships between TMT to kinematic variables. Results The stroke group had significant slower TMT (mean difference 2.6 s, d  = 1.33) than the control group, and six other kinematic variables showed significant group differences. At matched speeds, the stroke group had lower accuracy and excessive scapular and trunk movements compared to controls. Pointing time and elbow flexion during the pointing phase were most related to stroke severity. For the stroke group, the number of movement units during the pointing phase showed the strongest association with the TMT, and explained 60% of the TMT variance. Conclusions The timed FNT discriminates between persons with mild and moderate upper limb impairments. However, kinematic analysis to address construct validity highlights differences in pointing movement post-stroke that are not captured in the timed FNT.